Pelagic Nekton Abundance and Distribution in the Northern Sacramento–San Joaquin Delta, California. Issue 1 (2nd January 2017) - Feyrer, Frederick; Slater, Steven B.; Portz, Donald E.; Odom, Darren; Morgan-King, Tara; Brown, Larry R.
Abstract: Knowledge of the habitats occupied by species is fundamental for the development of effective conservation and management actions. The collapse of pelagic fish species in the Sacramento–San Joaquin Delta, California, has triggered a need to better understand factors that drive their distribution and abundance. A study was conducted in summer–fall 2014 in an attempt to identify physical and biological habitat conditions that drive the abundance and distribution of pelagic species in the northern region of the system. The study was conducted in the three largest channels in the northern Sacramento–San Joaquin Delta by dimension, volume, and flow capacity. The pelagic community was dominated by three nonnative species, Siberian prawn Exopalaemon modestus, which comprised 56% of the total number of organisms, and two fish species, Threadfin Shad Dorosoma petenense and Mississippi Silversides Menidia audens, which together comprised 43% of the total number of organisms. Total fish and total shrimp abundance were sensitive to the most extreme values of turbidity and temperature encountered and positively associated with total zooplankton biomass. The results suggested that habitat conditions in terminal channels, historically a common feature on the landscape, support higher abundances of pelagic species and zooplankton than open-ended channels. These results provide resource managers with useful information on the habitat associations of pelagic species and on how the future distribution and abundance of pelagic species will likely change in response to climate or other ecological factors. Received March 8, 2016; accepted September 22, 2016